Impacts of climate change and pumping on groundwater resources in the Kou River basin, Burkina Faso - Tirogo, Justine; Jost, Anne; Biaou, Angelbert; Koussoubé, Youssouf; Ribstein, Pierre; Dakouré, Denis (Comptes Rendus. Géoscience)
West Africa is subject to climatic variability with a long period of drought during the 1970s–1990s whose impact on groundwater remains poorly studied. This work focuses on the Kou basin in Burkina Faso, which holds a large groundwater resource resulting in exceptional springs. This resource shows signs of depletion that raise a critical question: What is the share of climate and that of withdrawals in the depletion of the resource? To answer this question, we used a hydrogeological model calibrated in steady state and in transient regime (monthly time step 1995–2014; annual time step 1961–2014). The results showed that pumping has a significant impact on the resource, especially in the vicinity of the pumping areas, and caused approximately 30% of the observed decrease in spring discharge. Drought periods and consecutive years without recharge also led to a decrease in groundwater levels. Thus, precipitation deficits and variability, combined with increasing pumping, have endangered the resource.